A test of the Kryonerion ``seeing'' with DIMM equipment - Mislis, D.; Harlaftis, E. T.; Buckley, D.; Gazeas, K.; Stathoulis, K.; Dimou, G.; Seiradakis, J. H. (Recent Advances in Astronomy and Astrophysics, 2006)
We present a test-study of the ``seeing'' at the Kryonerion Station of the National Observatory of Athens. We used a Differential Image Motion Monitor (DIMM) during July and October 2002 and found a median ``seeing'' of 0.68 arcseconds and 1.42 arcseconds, respectively. We also compared the technique against the Hartmann-version of the ESO-type DIMM method and found similar results within 0.05 arcseconds. For some reason, which is under investigation by international teams, the measurements of our ESO-type DIMM are underestimated by ~ 10% compared to ESO-standard DIMM measurements. Simultaneous ESO-type DIMM measurements and standard gauss-fitting-technique measurements, taken with the Kryonerion 1.2m telescope (inside the dome) indicate that the ``seeing'', as measured by the telescope is by 1 arcsecond larger. The above tests were performed in order to calibrate, test and make a brief sampling of the ``seeing'' at the Kryonerion Station with the aim to move eventually the equipment to the Emilios Harlaftis Astronomical Station the site of the new 2.3m ARISTARCHOS telescope - for a long-term ``seeing'' monitoring. As a by-product of this project, a new DIMM Station became operational at Mt. Holomon, in the premises of the University of Thessaloniki, in 2004.
Keywords: 95.45.+i; 95.55.-n; Astronomical and space-research instrumentation; Observatories and site testing